Uncoupling of influenza A virus transcription and replication through mutation of the unpaired adenosine in the viral RNA promoter. - te Velthuis, A; Turrell, L; Vreede, F; Fodor, E (2013)
Transcription and replication of the influenza A virus RNA genome are mediated by the viral RNA polymerase from a promoter consisting of the partially base-paired 3' and 5' termini of viral genome segments. Here we show that transcription and replication can be uncoupled by mutation of an unpaired adenosine in the 5' strand of the promoter. This residue is important for transcription but not replication by being essential for the cap-binding activity of the RNA polymerase.